THE FINAL STATE ATTESTATION IN MAGISTRACY: PRACTICE-ORIENTED FORMAT - Tatiana V. Tatianina; Tatiana I. Shukshina (Высшее образование в России)
The article describes the content related and procedural aspects of the state final certification of graduates of Master's degree programs of the profile "Higher Education Pedagogy". The authors give the examples of the original practice-oriented tasks for proficiency tests, and the tools for their assessment.